INVESTIGATION OF THE EXTRACTION KINETICS OF MARIGOLD BY ETHANOL - Vladimir Damjanović; Vladan Mićić; Žika Lepojević (Journal of Engineering & Processing Management, 2012)
Marigold (Calendula officinalis L.) defined the particle size was extracted using 40, 50 and 60% ethanol as a solvent by classical procedure of maceration. The kinetics of extraction by given ethanol concentrations in relation to drug:solvent = 1:10 was studied. The quantity of total substances (q0, g/100g drugs), and the quantity of the residue substances which can be extracted from the drugs (qi, g/100g drugs) during the extraction were determined. On the basis of experimentally obtained values of qi , q0 and τ, coefficient of fast extraction (b*) and coefficient of slow extraction (k) were calculated. The obtained results show that by using 40% ethanol as solvent the coefficient of fast extraction has been the highest value. With using other two solvents the coefficient of fast extraction has been the same value. These results are in agreement with the theoretical assumption that the fastest solubility is achieved in the most polarity solvent.
Keywords: extraction; ethanol; marigold; coefficient of fast extraction